Income Smoothing, Displaced Commercial Risk and Bankruptcy in Indonesian Islamic Banks During the COVID-19 Pandemic - Laela, Sugiyarti Fatma; Latif, Abdul (Accounting Department, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jawa Timur, 2023)
This research seeks to examine how the COVID-19 pandemic has influenced shifts in income smoothing practices within Islamic banks in Indonesia. It also investigates the effect of income smoothing on displaced commercial risk (DCR) and the influence of DCR on the potential for bankruptcy in Islamic banks. Using a quantitative approach, the study employs a mean difference test and panel data regression through path analysis in relation to 13 Islamic banks over two 21-month periods before the pandemic (July 2017 to March 2019) and during the pandemic (April 2019 to December 2020). The findings reveal significant differences in income smoothing behavior between the pre-pandemic and pandemic periods, with income smoothing negatively affecting DCR. Furthermore, a lower DCR leads to a lower bankruptcy risk, as measured by the z-score. These results highlight the interconnectedness of income smoothing, commercial risk management, and financial stability in Islamic banks during periods of economic uncertainty. The study concludes that Islamic banks need to enhance risk management strategies to mitigate the effects of external economic shocks.